The Universal Shape of Economic Recession and Recovery after a Shock - Damien Challet; Sorin Solomon; Gur Yaari (Kiel Institute for the World Economy (IfW), 2009)
We show that a simple and intuitive three-parameter equation fits remarkably well the evolution of the gross domestic product (GDP) in current and constant dollars of many countries during the times of recession and recovery. We then argue that it can be used to detect shocks and discuss its predictive power. Finally, a two-sector theoretical model of recession and recovery illustrates how the severity and length of recession depends on the dynamics of transfer rate between the growing and failing parts of the economy.
Keywords: O23; C32; O41; 330; Economic growth; transition economies; GDP; modelling; prediction; optimal policy; Konjunktur; Zeitreihenanalyse; Schock; Konjunkturprognose; Prognoseverfahren; Mehr-Sektoren-Modell; Branchenkonjunktur; Theorie; Osteuropa